ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT INVESTASI DI PASAR MODAL - Shabrina, Dea Nurullyah; Habiburahman, Habiburahman (Buletin Studi Ekonomi; VOLUME.28.NO.02.TAHUN.2023DO - 10.24843/BSE.2025.v30.i01.p03, 2025)
This study aims to analyze the factors influencing investment interest in the capital market by examining the role of technological advancements, financial literacy, and risk perception. Using a quantitative approach, data were collected through questionnaires distributed to 100 respondents aged 20-24 years in Bandar Lampung City. The research instrument utilized a Likert scale with a score range of 1-5. Sampling was conducted randomly, and the data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that all three variables significantly influence investment interest. Technological advancements facilitate access to the capital market, financial literacy enhances individuals' understanding of financial management, and a well-managed risk perception fosters confidence in investing. Risk perception was found to be the most dominant factor influencing investment decisions. These findings highlight the importance of financial education and technology utilization in increasing investment participation, especially among young generations. Therefore, improving financial literacy and risk perception is recommended as a key strategy to attract more investors to the capital market.